Pemanfaatan Digital Marketing untuk Meningkatkan Pemasaran Produk Makanan dan Brand Awareness Desa Kraton - Dimas Bastara Zahrosa; Pamuji, Mutiara Balquis; Damascena, Cindera Rosa; Soejono, Djoko; Mulyo Aji, Joni Murti (ABDIKAN: Jurnal Pengabdian Masyarakat Bidang Sains dan Teknologi, 2024)
Kraton Village is one of the villages in Jember Regency, precisely in Kencong District. Kraton Village has a population of 10,534, and 1,756 of them are households. Kencong District has several villages, including (1) Kraton Village, (2) Cakru Village, (3) Paseban Village, (4) Kencong Village, and (5) Wonorejo Village. Kraton Village itself consists of several hamlets, namely (1) Krajan Hamlet, (2) Sidonganti Hamlet, (3) Muneng Hamlet, and (4) Kedunglangkap Hamlet. A brand is a name, term, sign, symbol, design, or a combination of these that is intended to identify the product or service of a person or seller and to differentiate it from competitors' products or other similar products. Understanding brand awareness. Brand awareness is the ability of consumers to recognize or remember that a brand is a member of a certain product category. So in a business, the name or label becomes as important as the identity of a product. Service activities have been completed and reported in the form of an article in January 2024. The results of the implementation of this service generally help in the process of optimizing the food business in Kraton Village, both online and conventionally. With this program, food businesses are not only invited to sell products and market them online but are also invited to create innovative, creative products that can generate consumer interest in buying these products.